Phylogenetic relationships between the six superoxide dismutase proteins (FeSOD) of Trichomonas vaginalis and FeSOD6 genetic diversity - Hwang U.W; Shin K.S.; Ryu J.S.; Min D.Y.; Ahn M.H. (Parasite, 2002)
The parasitic protozoan Trichomonas vaginalis is known to contain several types of Fe-containing superoxide dismutase proteins (FeSOD). Using three different methods of phylogenetic analysis, maximum parsimony (MP), neighbor joining (NJ), and maximum likelihood (ML) methods, we examined the phylogenetic relationships among the six FeSOD (FeSOD1-FeSOD6) based on their amino acid sequences. All the analyses consistently suggested that the six proteins formed a monophyletic group implying that they probably be originated from an ancestral protein form through repeated duplication events. Although MP tree was totally unresolved, the NJ and ML trees revealed that FeSOD6 placed the most basal position and thus emerged earlier than the other five gene types during the evolution of T. vaginalis. Phylogenetic relationships among the five remaining proteins were (FeSOD2, FeSOD3), (FeSOD4, (FeSODl, FeSOD5)) although weakly supported in terms of bootstrapping values. In addition to this, we newly designed two PCR primer specifically amplifying full-length FeSOD6 gene and examined its genetic diversity among 1 2 T. vaginalis isolates from five countries and three continents. They had the same nucleotide sequences except those of three Korean isolates which showed one to three different nucleotides